The PhD parenthood trap : caught between work and family in academia - Crawford, Kerry F.; Windsor, Leah C. (Washington, DC : Georgetown University Press, 2021)
"The PhD Parenthood Trap gives voice to the struggles lived by parents in academia and identifies avenues to better approaches. Kerry F. Crawford and Leah C. Windsor present insights from original survey data and vignettes that they have collected from scholars across disciplines. Topics include pregnancy, miscarriage and infant loss, family leave, breastfeeding, daily parenting challenges, and more. The authors have found that universities and their departments are displaying a lack of understanding, uniform policies, support, and flexibility for family formation and parenting, which is hurting the career development of parent-scholars, especially women. The authors conclude each chapter with recommendations for best practices and needed changes in order to make academia an exemplar of progressive family leave policies. The PhD Parenthood Trap is a rallying cry for parents in academia and it also seeks to educate university and department administrators in order to encourage meaningful change"--
Surviving or Thriving? The State of Parenthood in the Academy -- Thesis Baby : Getting Student-Parents the Support they Need -- How to Scale the Ladders While Sidestepping the Chutes : On Parenting without the Security of Tenure -- The Elusive Work-Life Balance : Daily Challenges in Academic Parenting -- Doctor, Parent : Recognizing the Range of Experiences -- Sick and Tired : The Physical Toll of Parenthood -- Love, Loss, and Longing : Fertility Struggles, Adoption, Miscarriage, and Infant/Child Loss -- Express Yourself : Breastfeeding and Lactation in the Ivory Tower -- Looking Back, Moving Forward : Conversation Starters for a More Inclusive Academic Environment
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: Women college teachers -- United States -- Social conditions; Women in higher education -- United States -- Social conditions; Women graduate students -- United States -- Social conditions; Working mothers -- United States; Work and family -- United States; Work-life balance -- United States; Professeures (Enseignement supérieur) -- États-Unis -- Conditions sociales; Femmes dans l'enseignement supérieur -- États-Unis -- Conditions sociales; Mères au travail -- États-Unis.; Travail et familles -- États-Unis.; Conciliation travail-vie personnelle -- États-Unis.; EDUCATION / Higher; Women college teachers -- Social conditions; Women graduate students -- Social conditions; Work and family; Work-life balance; Working mothers; United States; Electronic book